OPTIMALISASI PENJUALAN ONLINE UNTUK KELOMPOK USAHA KONVENSIONAL DI KELURAHAN BOJONG, KECAMATAN PONDOK TERONG, DEPOK - Putri, Dyah Puspitasari Sunaryo; Bakti, Prayoga; Supono, Ihsan; Zulziar, Marjuki; Wibowo, Priyo (LPPM Universitas Pamulang, 2020)
In the early of 2020 the world was shocked by the presence of the Covid-19, a virus with a very rapid spread and became the highest cause of death in the world. Indonesia is among of countries that heavily affected by this virus. Various policies are implemented so that the spread chain of the virus is broken, ranging from work from home, physical distancing to Large Scale Social Restrictions (PSBB). The impact of PSBB is also felt by offline shop owners who are forced to close their shops due to activity restrictions, which causes a loss of income or a drastic reduction in sales turnover. Due to the pandemic, business owners are required to do efforts to adapt to current conditions, one of which is utilizing technology in conducting online sales. Bojong Village, Pondok Terong Subdistrict, is an area that has many private business owners and MSMEs. In regard of the above problems statement, the Community Service Group (PKM) of the Industrial Engineering Study Program at the University of Pamulang held a training on the optimization of online sales during the Covid-19 pandemic for conventional business groups. It is expected that this training can increase the understanding of PKM participants using online sales technology to maintain their business.